Development of Mathematics E-LKPD with Flat Building Materials Using the Wizer.Me Website Application to Support Differentiated Learning - Apriani, Rintan; Pamungkas, Aan Subhan; Rakhman, Patra Aghtiar (CV. Rayyan Dwi Bharata, 2025)
This research aims to determine the feasibility and determine students' responses to the use of E-LKPD mathematics learning media with flat building materials with the wizer.me website application to support differentiated learning in class V elementary schools. This research uses a Research and Development (RD) approach. The subjects in this research were 20 class V students. The research results show that in terms of feasibility, based on media expert validation, an average percentage score of 95% was obtained in the